2015
DOI: 10.1590/0103-8478cr20140198
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological control of Sclerotinia stem rot in the soybean crop

Abstract: It was evaluated the effect of fungicides and the microbial control agent Trichoderma harzianum on the inhibition of the carpogenic and ascospore germination of 2010-11, reduziram em 75,7 e 77,6%, respectivamente.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
(10 reference statements)
1
12
1
4
Order By: Relevance
“…Contrary to our study, isolated fungicide active ingredients (not mixed with other active ingredients) and isolated treatments of T. harzianum in two consecutive harvests were shown to be more efficient at controlling the severity and incidence of WM and improving yield than treatments containing pure fungicides (fluazinam) in the 2009-2010 crop (Sumida et al, 2015).…”
Section: Codecontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our study, isolated fungicide active ingredients (not mixed with other active ingredients) and isolated treatments of T. harzianum in two consecutive harvests were shown to be more efficient at controlling the severity and incidence of WM and improving yield than treatments containing pure fungicides (fluazinam) in the 2009-2010 crop (Sumida et al, 2015).…”
Section: Codecontrasting
confidence: 99%
“…When pyrisoxazole (rarely used in Brazil) was used to control 166 strains of Sclerotinia sclerotiorum, it provided excellent protection and reduced disease in oleaginous plants (Duan et al, 2018). The fungicides procymidone and fluazinam (commonly used in Brazil) combined with benzalkonium chloride were more efficient in controlling WM in soybeans (73.1 -71.6%, 2010 crop; 75.7 -77.6 %, 2011 crop) than isolated applications of T. harzianum (Sumida et al, 2015).…”
Section: Codementioning
confidence: 99%
“…Additionally, in a study by Sumida et al . (), application of T. harzianum did not inhibit sclerotial germination relative to the untreated control, despite several reports of its efficacy (Zeng et al ., ; de Aguiar et al ., ).…”
Section: Biological Controlmentioning
confidence: 99%
“…It has also been shown that different strains of S. sclerotiorum that produce varying amounts of oxalate are differentially susceptible to C. minitans (Huang et al, 2011). Additionally, in a study by Sumida et al (2015), application of T. harzianum did not inhibit sclerotial germination relative to the untreated control, despite several reports of its efficacy (Zeng et al, 2012a;de Aguiar et al, 2014).…”
Section: Biological Controlmentioning
confidence: 99%
“…The integrated management of SSR utilizes a combination of cultural, chemical, and biological control practices (Peltier et al 2012). Some practices may include, crop rotation using nonhost crops (Gracia-Garza et al 2002;Mueller et al 2002aMueller et al , 2002bRousseau et al 2007), practicing reduced tillage (Gracia-Garza et al 2002;Kurle et al 2001;Mueller et al 2002a, b), using resistant cultivars (Grau et al 1982;Hoffman et al 2002;Kurle et al 2001), modifying the soybean canopy through seeding rate and row spacing (Jaccoud-Filho et al 2016;Kurle et al 2001;Lee et al 2005), and applying inseason chemical control (Mueller et al 2004;Peltier et al 2012;Sumida et al 2015;Saharan and Mehta 2008) (Fig. 1).…”
Section: Integrated Managementmentioning
confidence: 99%